Development of erosion-corrosion mechanisms for the study of steel surface behavior in a sand slurry - Naz, M.Y. (Elsevier B.V., 2017)
In this study, dry sand impact and linear polarization resistance (LPR) monitoring techniques were used to study the detrimental effects of the sand size on surface morphology of the mild steel. An electrochemical mechanism was developed to measure the resistance of the metal coupons rotating in a slurry of 4 wt NaCl and 5 wt sand. Scanning probe microscopy (SPM) and hardness testing of the eroded coupons were conducted to elaborate their surface topography. In-depth analysis revealed that not only the larger particles but smaller particles as well caused significant erosion-corrosion of the steel coupons. It was noticed that hardness and density of the erodent particles were reasonably high to induce the plastic deformation and micro-structures at the metal surface. The LPR measurements revealed high coupon resistance in the fine sand slurry than in the coarse sand slurry. The localized corrosion and erosion-corrosion attacks on the metal surface were also supplemented with the stirring rate and the presence of NaCl in the solution. The corrosion rate was sharply increased with an increase in stirring rate above 500 rpm. © 2017 Elsevier Ltd